Development of mitochondrial 12S rRNA gene for identification of dog and rat in beef using multiplex PCR - Cahyadi, M.; Taufik, I. M.; Pramono, A.; Abdurrahman, Z. H. (Journal of the Indonesian Tropical Animal Agriculture, 2019)
The 12S rRNA gene is one of unique regions in mitochondrial genome usually used for phylogenetic studies and species identification. The objective of present study was to develop species specific primers from mitochondrial 12S rRNA gene for identification of dog and rat in beef by using multiplex PCR assay. Three primer pairs of mitochondrial 12S rRNA gene specific for bovine, dog and rat were designed and selected to evaluate their specificity and fidelity. Moreover, a total of twelve DNA samples extracted from meat tissue were also prepared to test those primers using simplex and multiplex PCR. The PCR products were then visualized using 2% of agarose gel under the UV light and three of them were sequenced. In addition, sequence data were analyzed using Clustal Omega software and BLAST. The result showed that simplex PCR assay successfully amplified DNA targets which are respectively indicated by 155 bp (bovine), 244 bp (dog), and 491 bp (rat) of DNA bands. Furthermore, DNA sample sequences were identically similar to reference sequence used in this study. Multiplex and simplex PCR analyses also indicated that these primer pairs specifically amplified DNA target for each species in the samples containing various species. The results suggested that designed primers in this study could be used to identify dog and rat in raw beef containing these species meat. Further experiment should be conducted using meat-processed products and commercial meat products as samples.